A personality-based behavioural model: Susceptibility to phishing on social networking sites - Frauenstein, Edwin Donald (Rhodes University, Faculty of Commerce, Department of Information Systems)
The worldwide popularity of social networking sites (SNSs) and the technical features they offer users have created many opportunities for malicious individuals to exploit the behavioral tendencies of their users via social engineering tactics. The self-representation and social interactions on SNSs encourage users to reveal their personalities in a way which characterises their behaviour. Frequent engagement on SNSs may also reinforce the performance of certain activities, such as sharing and clicking on links, at a "habitual" level on these sites. Subsequently, this may also influence users to overlook phishing posts and messages on SNSs and thus not apply sufficient cognitive effort in their decision-making. As users do not expect phishing threats on these sites, they may become accustomed to behaving in this manner which may consequently put them at risk of such attacks. Using an online survey, primary data was collected from 215 final-year undergraduate students. Employing structural equation modelling techniques, the associations between the Big Five personality traits, habits and information processing were examined with the aim to identify users susceptible to phishing on SNSs. Moreover, other behavioural factors such as social norms, computer self-efficacy and perceived risk were examined in terms of their influence on phishing susceptibility. The results of the analysis revealed the following key findings: 1) users with the personality traits of extraversion, agreeableness and neuroticism are more likely to perform habitual behaviour, while conscientious users are least likely; 2) users who perform certain behaviours out of habit are directly susceptible to phishing attacks; 3) users who behave out of habit are likely to apply a heuristic mode of processing and are therefore more susceptible to phishing attacks on SNSs than those who apply systematic processing; 4) users with higher computer self-efficacy are less susceptible to phishing; and 5) users who are influenced by social norms are at greater risk of phishing. This study makes a contribution to scholarship and to practice, as it is the first empirical study to investigate, in one comprehensive model, the relationship between personality traits, habit and their effect on information processing which may influence susceptibility to phishing on SNSs. The findings of this study may assist organisations in the customisation of an individual anti-phishing training programme to target specific dispositional factors in vulnerable users. By using a similar instrument to the one used in this study, pre-assessments could determine and classify certain risk profiles that make users vulnerable to phishing attacks.
Keywords: Phishing; Social networks; Personality; Self-presentation in mass media; Internet fraud; Internet users -- Habits and behavior; Big Five model; Human information processing; Heuristic-Systematic Model (HSM)